Foreign Language Anxiety in ESP Courses: Analyzing Factors Among Business Digital, Cyber Security, and Tax Accounting Students - Yuliyanti, Novy; Romadhon, Romadhon (Universitas Muria Kudus, 2025)
This study explores Foreign Language Anxiety (FLA) among students in English for Specific Purposes (ESP) courses across three majors: Business Digital, Cyber Security, and Tax Accounting. FLA, characterized by apprehension in language learning, significantly impacts students’ academic performance, particularly in specialized fields where language proficiency is crucial. Using the Foreign Language Classroom Anxiety Scale (FLCAS), the study assessed communication apprehension, test anxiety, and fear of negative evaluation among 160 first-year polytechnic students. The results indicated that Business Digital students reported the highest overall anxiety, particularly due to fear of peer ridicule during speaking activities. Cyber Security students experienced significant anxiety related to comparisons with peers, feeling less competent in language skills. Conversely, Tax Accounting students showed the lowest anxiety related to correction feedback, reflecting a tolerance for learning from mistakes. The findings suggest that each major's unique demands shape the nature of FLA, highlighting the need for tailored instructional strategies to mitigate anxiety and enhance language learning in ESP contexts.